Laparoscopic Appendectomy in the Days of COVID-19. Issue 5 (27th October 2021) - Abramov, Roi; Neymark, Mariya; Harbi, Asaf; Gilshtein, Hayim
Abstract : Background: Acute appendicitis is one of the most common emergencies treated by general surgeons. The treatment of choice in the majority of cases is laparoscopic appendectomy. In the era of the COVID-19 pandemic, there is a concern for a delayed referral of patients and thus a more advanced presentation of the disease leading to a prolonged and complicated course. Methods: Retrospective review of a computerized database of patients who were admitted with acute appendicitis and underwent laparoscopic appendectomy during the COVID pandemic in a single tertiary center in Israel. Patients were compared with those who were admitted and operated for appendicitis in the same period in the previous year. Results: One hundred twenty-three patients underwent laparoscopic appendectomy in the study period in 2020, compared with 109 who had surgery in 2019. During the COVID pandemic 41 patients presented with complicated appendicitis versus 22 patients in 2019 ( P =0.0174). The placement of peritoneal drains was more prevalent during the pandemic, 5.5% versus 11.4%, and the use of stapler device for appendicular stump closure ( P =0.0105). Conclusions: During the first stage of the COVID-19 pandemic, there was a significant increase in the rate of complicated appendicitis. Patients should be strongly encouraged not to refrain from medical treatment and go to the emergency room with the persistence of symptoms.